The Effect of Discipline and Motivation on Teacher Achievement in Elementary Schools - Dine Trio Ratnasari; Udin Syaefudin Sa'ud; Mubiar Agustin; Johar Permana (STAI Hubbulwathan Duri, 2023)
Competency tests were conducted to obtain information about mastery of teaching materials (substances) and learning methods for each teacher. This research was conducted with one dependent variable, namely teacher teaching performance (Y), and two independent variables, namely discipline (X1) and motivation (X2). This study uses a descriptive method with a quantitative approach. The temporary design research used is survey design research. The research instrument used was a questionnaire using a Likert scale as an assessment of the score for each question, with a score range of 1–5. The study population was all schools in Lebak Regency, totaling 775 schools. The research sample used a stratified random sampling technique. The results of this Discipline study have an influence and are significant on the performance of teaching teachers, including the high category. Motivation has a significant effect on teacher teaching performance in the high category. It can be concluded that discipline and motivation have high cross-category scores in achieving teacher-teaching performance.